Evaluating the User’s Satisfaction of Applying Information System Based on EDUSOFT in Managing Students’ Data at Da Lat University - Phan, Thanh Đồng (H. : ĐHQGHN, 2017)
VNU Journal of Science: Education Research ; Vol. 30, No. 2 (2014) ; p. 36-43